2018
DOI: 10.1002/cctc.201800427
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Strong Lewis Base Sites on Glucose Hydrogenolysis

Abstract: This work reports the individual role of strong Lewis base sites on catalytic conversion of glucose hydrogenolysis to acetol/lactic acid, including glucose isomerisation to fructose and pyruvaldehyde rearrangement/hydrogenation to acetol/lactic acid. La2O3, Nd2O3, Sm2O3, and Pr6O11 were selected as representative oxides consisting of different base sites. The basicity of these lanthanide oxides was characterised by CO2‐TPD and DRIFT spectroscopy. It was found that lanthanide cation‐oxygen pairs, Brønsted OH gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…MgO is strongly basic, and thus in our system, isomerization of D‐glucose to fructose may have been enhanced either by MgO or by Mg(OH) 2 generated from MgO. Fructose is converted to glyceraldehyde and dihydroxyacetone by a retro‐aldol reaction, which involves C−C bond cleavage and is reported to be enhanced by base catalysts [35,36] . We previously reported that both dihydroxyacetone and glyceraldehyde can be converted to lactic acid in water in the absence of a catalyst even at 473 K [24] …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…MgO is strongly basic, and thus in our system, isomerization of D‐glucose to fructose may have been enhanced either by MgO or by Mg(OH) 2 generated from MgO. Fructose is converted to glyceraldehyde and dihydroxyacetone by a retro‐aldol reaction, which involves C−C bond cleavage and is reported to be enhanced by base catalysts [35,36] . We previously reported that both dihydroxyacetone and glyceraldehyde can be converted to lactic acid in water in the absence of a catalyst even at 473 K [24] …”
Section: Resultsmentioning
confidence: 84%
“…Fructose is converted to glyceraldehyde and dihydroxyacetone by a retro-aldol reaction, which involves CÀ C bond cleavage and is reported to be enhanced by base catalysts. [35,36] We previously reported that both dihydroxyacetone and glyceraldehyde can be converted to lactic acid in water in the absence of a catalyst even at 473 K. [24]…”
Section: Mechanism Of Chitin Conversion To Lactic Acidmentioning
confidence: 99%
“…In addition, Mg(OH) 2 increased the isomerization reaction [103].In chitin conversion system, we used MgO and Mg(OH) 2 (MgO is hydrolyzed to Mg(OH) 2 ) could be increase isomerization reaction. In next step, glyceraldehyde and dihydroxyacetone were obtained from fructose by retro-aldol reaction, which enhanced by base catalyst [103,122]. From previous research lactic acid could be converted from dihydroxyacetone and glyceraldehyde in water solvent [31].…”
Section: Reaction Condition Of Chitin Conversion With Catalystmentioning
confidence: 99%